Microclimate and heat unit requirement of maize (Zea mays L.) under different thermal environments, mulching and irrigation levels - Rani, Radha; Singh, Som Pal; Kingra, P K (Annals of Agricultural Research, 2017)
An experiment was conducted at the research farm of School of Climate Change and Agricultural Meteorology, PAU, Ludhiana to study the effect of two dates of sowing (D1: 1st August and D2: 15th August), mulching (Mo: no mulch and M1: straw mulch @6 t ha–1) and three irrigation levels (IW:CPE = 0.50, 0.75 and 1.00) on microclimate and heat unit requirement of maize during kharif 2010. Photosynthetically active radiation (PAR) interception and relative humidity were higher in earlier sown mulch applied crop under IW:CPE = 0.75 level of irrigation. Daytime soil temperature was observed to be lower under mulch application as compared to no mulch, however night time temperature was slightly higher under mulch application. The data indicates that crop duration was lengthened and higher degree days were consumed in the earlier sown mulch applied crop under irrigation of IW:CPE = 0.75. Crop sown on 1st August irrigated at IW:CPE of 0.75 with mulch application @ 6.0 t ha–1 had most favourable microclimate supporting the yield parameters. Growing degree days depicted positive and linear relationship with maize yield (R2 = 0.79) and harvest index (R2 = 0.62). Such microclimatic modifications can be highly beneficial for alleviation of heat and water stress under changing climate and water limiting scenarios in future.